Drug Use Profile: In The Process of Drug Discontinuation at Mataram City Hospital in 2023 - Evi Fatmi Utami; Alfiansyah R (Journal Scientific of Mandalika (JSM) e-ISSN 2745-5955 | p-ISSN 2809-0543, 2025)
Automatic Stop Order (ASO) is an action taken by​ pharmacist for stop treatment patient with reason certain when patient be at home pain and duration of use determined by Team Hospital Pharmacy and Therapy. To get an overview usage drug ASO at Mataram City Hospital Year 2023. Research methods used​ in study. This is study observational and using design descriptive retrospective. Results Overview of use drug ASO started with characteristics like type sex own presentation that is man man as many as 8 patients (53.33%) while for type sex woman alone 7 patients (46.67%). And for characteristics age Patient in range age 1 5 -2 5 years is 1 Patient (6.67%). Meanwhile range age 2 6 -4 5 year is 6 Patients (40%) and range age 46-65 years is 8 Patients (53.33%). The highest use of drugs in the Antibiotic group was Ceftriaxone 7 (26.92%), Cefoperozone 7 (26.92%), Meropenem 1 (3.84%) followed by the Analgesic-antipyretic group, namely Ketorolac 2 (7.69%) and Paracetamol 9 (34.61%). From the interview results, it can be concluded that the use of drug in the process of termination medicine (ASO) at Mataram City Hospital 2023 is already rational.